Pembelajaran di Era Pandemi (Transformasi Pembelajaran Dimasa Pandemi : dari Tatap Muka ke Dunia Maya) - Nurul Latifa Hasibuan; Maulidia Utami; Cut Kumala Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The COVID-19 pandemic has had a major impact on the world of education, forcing a massive transformation of learning from face-to-face to the virtual world. In this article, we emphasize how technology, digital media, and online learning strategies have changed during the pandemic and how they are applied at various levels of education. In the online learning process, both teachers and students face challenges and opportunities, according to literature research conducted in several recent books and journals. Information technology is very important to convey information and encourage students to learn. This transformation not only affects learning methods but also requires innovation in curriculum and teaching methods to be more flexible and adaptive. The digital era has encouraged the use of technology in education. This is despite many obstacles, such as limited infrastructure and lack of human resources. This study shows that the readiness of the education system to face the crisis is very important. In addition, in the future, educators and students must be strengthened in digital skills.